2018
DOI: 10.1002/jts.22274
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Posttraumatic Stress Disorder on Health Functioning in Active‐Duty Military Service Members

Abstract: Researchers have suggested that posttraumatic stress disorder (PTSD) is associated with significant healthcare burden and utilization of medical services. The purpose of this study was to examine the impact of PTSD symptoms on health functioning among active-duty military personnel. Participants in the study were 366 treatment-seeking service members who had returned from deployment and were participating in a larger PTSD treatment study. Assessments included measures of PTSD symptom severity, combat experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…More specifically, some studies have found that PTSD and depression equally impact functioning (e.g. disability in older veterans; Smith et al, 2020 ), PTSD impacts functioning more than depression (educational functioning in student veterans; Morissette et al, 2019 ), or depression impacts functioning more than PTSD (physical health functioning in service members; Asnaani et al, 2018 ). Future studies are needed to better understand which types of functioning are most impacted by depression.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, some studies have found that PTSD and depression equally impact functioning (e.g. disability in older veterans; Smith et al, 2020 ), PTSD impacts functioning more than depression (educational functioning in student veterans; Morissette et al, 2019 ), or depression impacts functioning more than PTSD (physical health functioning in service members; Asnaani et al, 2018 ). Future studies are needed to better understand which types of functioning are most impacted by depression.…”
Section: Discussionmentioning
confidence: 99%
“…As noted by McCaslin and colleagues (2016), the research on the relationship between severity of PTSD symptoms and impairment in functioning is mixed, with some, but not all, studies demonstrating an association between these variables. For example, a recent study of treatmentseeking service members found that PTSD severity was significantly associated with lower mental health functioning on the Veterans RAND 12-item Health Survey, whereas PTSD severity was not associated with worse physical health functioning (Asnaani et al, 2018), contrary to other research (Possemato, Wade, Andersen, & Ouimette, 2010). In addition, functioning can continue to be impaired even after a reduction or resolution of PTSD symptoms, suggesting that ameliorating symptoms may not be sufficient to effectively improve functioning (Bryant et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Keywords: PTSD, prolonged exposure therapy, military, trauma, non-inferiority Supplemental materials: https://doi.org/10.1037/ccp0000739.supp Posttraumatic stress disorder (PTSD) affects an estimated 7% of the population (Kessler et al, 2017), with higher rates among certain groups, including active-duty military personnel and veterans (Judkins et al, 2020). As PTSD severely impacts functioning (Asnaani et al, 2018;Creamer et al, 2011;Forbes et al, 2019), access to evidence-based treatment is imperative. Prolonged exposure (PE) therapy (Foa et al, 2007(Foa et al, , 2019) is an evidence-based treatment for PTSD with demonstrated efficacy across numerous populations, including military personnel (Foa et al, 2018;Peterson et al, 2019).…”
Section: What Is the Public Health Significance Of This Article?mentioning
confidence: 99%